Adsorption of procion red using layer double hydroxide Mg/Al - Muhammad Imron; Muhammad Said; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
Layer double hydroxide Mg/Al was synthesized by inorganic synthetic method. Material was characterized using FTIR and XRD analyses and used as adsorbent of procion red dye in aqueous medium. Factors that affect the adsorption process are adsorption time as the kinetic parameter; and the temperature and concentration of procion red as the thermodynamic parameter. FTIR spectra of layer double hydroxides showed unique vibration at wavenumber 1300 cm-1 and 1600 cm-1. Characterization using XRD shows diffraction angles at 29o, 27o, and 28o, which are typical of Mg/Al double layer hydroxides. Adsorption of procion red using layer double hydroxide Mg/Al resulted adsorption rate 7.1 minutes-1, maximum adsorption capacity 111.1 mg/g at 60 oC with increasing energy by increasing adsorption temperature. Keywords: Layered double hydroxides, adsorption, procion red.